Kajian Kitab Adab Al-Talibin Bagi Kelompok Ashabal-Suffah di Wonocolo Surabaya - Islamiyah (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2022)
Study of the book Riya>d al-Sa>lihi>n in Guwah hamlet, Rongdurin village, Tanah Merah, Bangkalan. The formulation of the problem raised in this community service activity is related to the lack of implementation of noble morals in everyday life. To find alternative solutions to the above, a study of the Adab Ṭalibīn book was held in an effort to improve the quality of religious knowledge for young people of the Ashab Al-Suffah group and to be able to apply good morals in everyday life. The objectives of this PKM activity are: 1. To equip youth with knowledge directly from original sources. 2. Increase the knowledge and morals of youth as a nation's generation with the substance of the book being studied. The problem solving framework designed in PKM activities in the form of implementing this training activity is: 1. Periodic explanation of materials. 2. Designing a weekly study of the Adab Ṭalibīn book every Monday night. 3. Evaluation of training results. Based on interviews, questions and answers and direct observations during the activity, this community service activity yielded the following results: first, increasing youth knowledge and understanding in the religious sphere, second, increasing youth knowledge and morals and being able to implement it in everyday life.